The end of employer-provided health insurance : why it's good for you, your family, and your company - Pilzer, Paul Zane; Lindquist, Richard (Hoboken : Wiley, 2015)
"The future of employer-provided health insurance is a #1 concern for business owners, financial executives and insurance professionals. Existing "health insurance" books focus only on public policy or consumers. Using the techniques outlined in this book, employers and their workers learn to save money on health insurance by migrating from group to individual plans at a total cost that is 20-60% lower for the same coverage (That's a savings of $4,000-$12,000 per year for a family of four). We are at the beginning of a huge transformation in the health insurance industry in which 120 million people are expected to move from group to individual insurance by 2025. Similar to the shift from defined benefit pensions to defined contribution 401(k) plans, the end of employer-provided health insurance will create opportunities for new entrants the way 401(k) plans led to the massive growth of Schwab, Fidelity and Vanguard"--
Machine generated contents note: Preface Executive Summary - Why You Should Read This Book Introduction - The End of Employer-Provided Health Insurance Part I - The Problem and The Solution CHAPTER 1: The Disadvantages of Employer-Provided Health Insurance CHAPTER 2: The Advantages of Individual Health Insurance CHAPTER 3: The Solution - Employer-Funded Individual Health Insurance PART II - How to Make Individual Health Insurance Work For You and Your Family CHAPTER 4: What is Individual Health Insurance? CHAPTER 5: How Much Does Individual Health Insurance Cost? CHAPTER 6: Premium Tax Credits - Are You Eligible for THE SUBSIDY? CHAPTER 7: When Can You Buy Individual Health Insurance? CHAPTER 8: Where Can You Buy Individual Health Insurance? CHAPTER 9: How to Choose Your Coverage - Bronze, Silver, Gold or Platinum CHAPTER 10: Networks - Choosing Your Doctors and Medical Providers CHAPTER 11: How to Select the Right Plan for You and Your Family CHAPTER 12: How to Reduce Your Individual Healthcare Costs PART III - How to Switch to Defined Contribution Healthcare CHAPTER 13: What is Defined Contribution Healthcare? CHAPTER 15: How to Implement to Defined Contribution Solution CHAPTER 16: How to Choose a Defined Contribution Solution Provider CHAPTER 17: How to Communicate Defined Contribution to Employees Appendix A: State-by-State Guide to Individual/Family Health Insurance Costs Appendix B: Is Your Company Required to Offer Employer-Provided Health Insurance? References List.
Includes bibliographical references and index.
Description based on print version record.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Health insurance -- Self-insurance -- United States; Health care reform -- United States; Electronic books